Synergistic proton transfer through nanofibrous composite membranes by suitably combining proton carriers from the nanofiber mat and pore-filling matrix - He, Y.; Zhang, H.; Li, Y.; Wang, J.; Ma, L.; Zhang, W.; Liu, Jian (R S C Publications, 2015)
© 2015 The Royal Society of Chemistry. Proton carriers are essential for highly conductive polymer electrolyte membranes. Herein, a series of nanofibrous composite membranes (NFCMs) are prepared by facilely incorporating a polymer matrix (sulfonated poly(ether ether ketone) (SPEEK) or chitosan (CS)) into a PVA/SiO2-based nanofiber mat. By changing the functional groups (acid, base or neutral) on the nanofiber mat, three types of composite proton carriers (I-type: acid-neutral or base-neutral, II-type: acid-acid or base-base, III-type: acid-base or base-acid) are generated at the interfacial domains of NFCMs. These carriers construct continuous conductive pathways by means of the inter-lapped nanofibers and inter-connected polymer matrix. Through the investigation of proton conductivities under both hydrated and low humidity conditions, it is found that NFCMs with I-type proton carriers show low proton conduction properties due to the deficient proton hopping sites. By comparison, II-type carriers display an increase of carrier loading amount, thus affording enhanced proton transfer abilities to NFCMs. III-type proton carriers (acid-base pairs) exhibit a distinct induction effect, by which protonation and deprotonation are promoted, resulting in superior low-energy-barrier proton hopping pathways. Thus, it is reasonable to state that the carrier loading amount and the interactions within them are both crucial to proton migration. In addition, the superior proton conduction abilities of III-type proton carriers confer favorable fuel cell performances on the NFCMs.